Solubility and Dissolution Rate Determination of Different Antiretroviral Drugs in Different pH Media Using UV Visible Spectrophotometer - K. Prakash; P. Narayana Raju; K. Shanta Kumari; M. Lakshmi Narasu (E-Journal of Chemistry)
Solubility and dissolution rate of three antiretroviral drugs such as lamivudine, zidovudine and stavudine was studied in four media having different pH. The samples were analyzed by using UV Visible spectrophotometer. lamivudine shows more solubility that is 276.08 mg/mL in 0.01 N HCl. Stavudine showing highest solubility that is 101.23 mg/mL in pH 4.5 acetate buffer. Zidovudine showing highest solubility that is 28.90 mg/mL in both water and 0.01 N HCl. All three drugs showing lower solubility in pH 6.8 phosphate buffer. Lamivudine and stavudine showing good dissolution rate in all media and showing similar release profiles and good correlation, whereas in zidovudine it was clearly observed a slower release at initial time points and then faster release profiles. The solubility and dissolution data in various media is helpful in predicting the bioavailability and also in dissolution method development.